A study to assess the knowledge regarding polycystic ovarian syndrome among the high school girls in a selected high school, Siliguri, West Bengal - Sarkar, Seema; Sharma, Sarda; Dutta, Barsha; Roy, Jayshree; Mahanta, Poulami; Das, Prity; Karmakar, Priyanka; Barman, Risha; Das, Samiksha; Barman, Sayantika; Dutta, Shreya; Ghosh, Soumili; et al. (International Journal of Research in Medical Sciences, 2024)
Background: Polycystic ovarian syndrome is a common reproductive and endocrine disorder found in 6-10% of the female population. The global prevalence of PCOS is estimated between 4% and 20%. The world Health Organization data suggest that approximately 116million women (3.45%) are affected by PCOS globally. The age standardized incidence rate of PCOS in women of reproductive age was 82.44 per 100000 in 2017, 1.45% higher than in 2007. Methods: There are many research designs, but among them we have chosen non-experimental research design for this study. Sample of this research study was 105 high school students of Little Angels’ Senior Secondary School, Siliguri through consecutive sampling technique. The instrument used to assess level of knowledge among high school girls was self-structured questionnaire. Results: Findings revealed that among high school girls 7.62% had poor knowledge, 26.67% had average knowledge, 64.76% had good knowledge and 0.95% had excellent knowledge about polycystic ovarian syndrome. Conclusions: The study concluded that the selected variables namely age, religion, educational class, exercise has significant impact on the knowledge regarding polycystic ovarian syndrome among high school girls. The study can be replicated with a larger sample to the findings can be generalized to a larger population.